Vassilis Alexakis and Dumitru Tsepeneag: otherness and exile (Colloquia Comparativa Litterarum, 2025)
The paper displays and analyses the characteristics of the writing of two authors from the Balkans who immigrated to France in the 1960s and 1970s – Vassilis Alexakis (of Greek descent) and Dumitru Tsepeneag (of Romanian descent). The study traces their critical reception in both France and the lost motherland and outlines certain peculiar features of the immigrant mentality and the complicated self-perception of the immigrants in the context of the dual reality of their existence. It also addresses the causes of the inability of the writers themselves and their literary characters to belong fully to one cultural heritage, and the identity issues that arise from this fact.
Keywords: Balkan literatures; migration; identity; otherness; Vassilis Alexakis; Dumitru Tsepeneag